Effect of infection on semen parameters in a sample of Iraqi infertile males. - Lazem, Ali A.; Al-Kaseer, Eman; Al-Diwan, Jawad K.; Al- Hadithi, Tariq S. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Several studies were carried out on association of infection with male infertility, which revealed great variations in the prevalence of genital infection in different parts of the world. This work was designed to study the effect of infection on semen parameters in a sample of Iraqi infertile males.Methods: A sample of 400 infertile male patients attending the High Institute for Embryo Research and Infertility Treatment for laboratory investigations and treatment were selected. This study was carried out during the period Nov. 2002 to April 2003, inclusive. Seminal fluid analysis was performed on samples obtained by masturbation into a glass container after 48 to 72 hours from of abstinence from sexual intercourse. Analysis (examination of volume, liquifaction, sperm count, motility percent, normal morphology percent and presence of pus cells) was performed within an hour after ejaculation.Results: Clinical infection was detected in 14% of infertile males and 29% had subclinical infection. Liquifcation time and leukocyte had significant variation between infected and non infected patients. Conclusion: Early diagnosis and treatment of genitourinary infection in necessary to reduce complication and infertility in future.